2010
DOI: 10.1186/1471-2458-10-242
|View full text |Cite
|
Sign up to set email alerts
|

The Nutrinet-Santé Study: a web-based prospective study on the relationship between nutrition and health and determinants of dietary patterns and nutritional status

Abstract: BackgroundNutrition-related chronic diseases such as cardiovascular diseases and cancer are of multiple origin, and may be due to genetic, biologic, behavioural and environmental factors. In order to detangle the specific role of nutritional factors, very large population sample cohort studies comprising precisely measured dietary intake and all necessary information for accurately assessing potential confounding factors are needed. Widespread use of internet is an opportunity to gradually collect huge amounts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
332
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 382 publications
(339 citation statements)
references
References 5 publications
3
332
1
3
Order By: Relevance
“…Over the past few years, increasing attention has been given to dietary patterns and their relationship to health outcomes such as CVD. [12][13][14][15][16][17][18][19][20] In intervention studies, specific dietary patterns of defined macronutrient composition are identified on the basis of expert evidence and a priori hypothesis (eg, the DASH or MED patterns) and then are evaluated in RCTs. In observational studies, associations between intake and risk factors are assessed.…”
Section: Introduction/rationalementioning
confidence: 99%
“…Over the past few years, increasing attention has been given to dietary patterns and their relationship to health outcomes such as CVD. [12][13][14][15][16][17][18][19][20] In intervention studies, specific dietary patterns of defined macronutrient composition are identified on the basis of expert evidence and a priori hypothesis (eg, the DASH or MED patterns) and then are evaluated in RCTs. In observational studies, associations between intake and risk factors are assessed.…”
Section: Introduction/rationalementioning
confidence: 99%
“…With the use of a dedicated website, the recruitment of adult volunteers (aged $18 y) is planned for 5 y with an additional follow-up of 10 y. The design, methods, and rationale of the study have been thoroughly described elsewhere (23). Briefly, to be included in the study, participants completed a set of questionnaires that focused on diet, physical activity, anthropometric measures, lifestyle, socioeconomic conditions, and health status.…”
Section: Populationmentioning
confidence: 99%
“…Volunteers aged 18 years or older (age range 18-96 years) living in France (urban and rural areas) and having access to the internet fill in self-administered web-based questionnaires at baseline and then regularly during follow-up using a dedicated, secured website. A detailed description of the NutriNet-Santé study has been published previously [16]. …”
Section: Methodsmentioning
confidence: 99%
“…It has been shown in large cohort studies that walking and/or cycling were associated with lower body weight, obesity prevalence, and percent body fat [12,13,14,15]. In a recent study on data from the NutriNet-Santé Web-cohort [16], we showed that walking at least 30 min/day or practicing any amount of cycling was associated with a lower BMI among French adults [17]. As indicated by a recent meta-analysis based on 23 randomized controlled trials published up to September 2012 (for a total of 1,201 participants), results from intervention studies also showed that being in the walking group was associated with a significantly lower BMI [18].…”
Section: Introductionmentioning
confidence: 99%